Printing Arab modernity : book culture and the American Press in nineteenth-century Beirut - Auji, Hala. (Arts and Archaeology of the Islamic World, 2016)
During the nineteenth century, the American Mission Press in Beirut printed religious and secular publications written by foreign missionaries and Syrian scholars such as Nāṣīf al-Yāzijī and Buṭrus al-Bustānī, of later nahḍa fame. In a region where presses were still not prevalent, letterpress-printed and lithographed works circulated within a larger network that was dominated by manuscript production. In this book, Hala Auji analyzes the American Press publications as important visual and material objects that provide unique insights into an era of changing societal concerns and shifting intellectual attitudes of Syria's Muslim and Christian populations. Contending that printed books are worthy of close visual scrutiny, this study highlights an important place for print culture during a time of an emerging Arab modernity.